Composition and residual stress analysis of Ti-Si/(Ti-Si)xN film on Mg–Al alloy substrate prepared by magnetron sputtering. (May 2015) - Li, H. T.; Wang, T.; Wang, Q.
<x content-type="archive" xml:space="preserve">Abstract</x> Chemical composition, residual stress and crystalline phase of Ti-Si/(Ti-Si)xN films were investigated with X-ray fluorescence and X-ray diffraction, respectively. The results reveal that the TiN phase has a preferential orientation along the crystalline plane (111). The residual stress in films is tensile stress, and the minimum stress reaches about 103 MPa under the deposition parameters of negative bias being 80 V and Ar/N2 flux ratio being 11/4. The element content decreases sharply with the negative bias greater than 80 V and Ar/N2flux ratio greater than 11/4. The composition and residual stress in the film can be controlled effectively by reasonably selecting fabrication parameters.